Applicability of protocols from high-income countries in a resource limited setting; real world data of histopathology, clinical features and long-term outcome of Hodgkin Lymphoma in Sri Lanka. (August 2021) - Hewamana, Saman; Kandabadage, Lakmali; Skandarajah, Thurairajah; Peiris, Natasha; Abeyaratne, Sobitha; Arseculeratne, Gehan; Perera, Eranga; Harischandra, Mahesh; Wijewickrama, Ananda; Somasundaram, Gnani; Srinivasan, Vadivelu; Somiah, Surjit; et al.
Abstract: Background: : There is a significant disparity in global cancer care and out-come between countries. We aimed to provide data on characteristics, average cost of treatment and survival estimates in patients with Hodgkin Lymphoma in Sri Lanka. Methods: All patients diagnosed with Hodgkin Lymphoma between 01.05.2013 and 01.10.2020 were included in the analysis. Findings: Classical Hodgkin Lymphoma(cHL) diagnosed in 85%; 68% presented with B symptoms and 61% had advanced stage of disease. Treatment was discontinued by 23% either before or just after starting treatment of whom 72% percent were females. The complete response (CR) rate of patients who continued treatment was 86% while the estimated five-year survival rate is 92%. Seventeen percent of these patients died but only two percent due to Hodgkin Lymphoma or associated treatment in the group which continued treatment compared to 45% in the group who defaulted treatment (p-value 0.0002). Five-year survival rate of patients who defaulted treatment was 50% while patients who continued treatment have an estimated five-year survival rate of 90%. Average cost of first line treatment was between US$ 2280 and US$ 7642. First treatment failure may incur substantially higher health care costs. Interpretation: This is the only well characterized study on long-term survival of patients with Hodgkin Lymphoma in Sri Lanka. We have shown that it is possible to successfully apply western treatment and supportive care protocols to the local population. This published data will help to bench mark and improve the treatment and develop blood cancer care in the local setting. Funding: None.